Role of Platelet-Rich Plasma in Healing after Impacted Mandibular 3rd Molar Surgery - N.S, Kedarnath; P.R, Abhilash (Journal of Orofacial Research, 2011)
Platelet-rich plasma (PRP), the concentrate of platelets in plasma contains various. Growth factors that enhance osseous regeneration. This prospective study was conducted, to compare the role of Platelet rich plasma in healing after impacted mandibular 3rd molar surgery. The study was performed by a single operator, all the patients underwent bilateral removal of mandibular 3rd molars and PRP that was prepared prior to start of the surgical procedure was placed into one of the extraction socket randomly selected by the author and the other side used as control. Clinical parameters like hypersensitivity reactions,pain, swelling, soft tissue healing, and dry socket were assessed. The bone fill and radiographic bone density were evaluated simultaneously. All the patients were followed up after the 1stday, 2ndday, 1week, 3-week, 2 months, 4months and after 6 months post operatively. Soft tissue healing differed significantly between PRP and NON-PRP sites. On radiographic evaluation significant differences were observed in the mean scores of radiographic density between PRPand NON-PRP sites on Photo Stimulating Phosphor (PSP) images and IOPA Radiographs. It was concluded that PRP contributed to better healing of soft tissues and bone and is a visible means of growth factory delivery. However, further studies are needed to substantiate our findings. It is the need of the hour for morecontrolled and scientific models, to assess the ultimate efficacy of PRP.